Vérification des performances de la colonne de débutaniseur au niveau de la section GPL Rhourde-Nouss - بالقط, اسماعيل; berrabah, bilal (University of El-Oued, 2021)
"The LPG plant facilities are designed to recover LPG and condensate remaining in the gas from phase A (gas treatment and condensate recovery). The exploitation of the RHOURDE NOUSS field (gas and condensate) over time has led to a decrease in the richness of heavy product. This decrease in richness influenced the operating parameters of the unit. Our work consists in making a verification calculation by approximate sizing method on the debutaniser column (T-02) and comparing the results obtained with the design one, to ensure the correct functioning of the column. " "تم تصميم مرافق مصنع غاز البترول المسال لاستعادة غاز البترول المسال والمكثفات المتبقية في الغاز من المرحلة أ (معالجة الغاز واستعادة المكثفات (. أدى استغلال حقل رود الناس (الغاز والمكثفات) بمرور الوقت إلى انخفاض ثراء المنتجات الثقيلة. أثر هذا الانخفاض في الثراء على إعدادات تشغيل الوحدة يتمثل عملنا في إجراء حساب تحقق من خلال طريقة التحجيم التقريبية على عمود نزعالبوتان (T-02) ومقارنة النتائج التي تم الحصول عليها مع التصميم، لضمان الأداء الصحيح للعمود. "
Génie Pétrochimie مذكرة ماستر تخصص
Keywords: LPG, Condensate, Debutanizer column (T-02), Approximate sizing method.; البترول المسال،المكثفات، عمود نزع البوتان (T-02)، طريقة التحجيم التقريبية.